Flood and Drought Analysis Of Godavari Sub Basin Based on Precipitation Index (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Godavari river is one of the largest river in the  India . Various government agencies are monitoring the hydrological flood and drought studies in the region, the most of the river flowing in the Maharashtra and Terengganu and Andhra prudish , states of India he  flood forecasting is based on the precipitation    classified  . The flood forecasting and drought scenarios like rain fall intensity, depth of run of water and, water levels and spread area over the study area has analyzed. Drought effects in aspect of irrigation    has also analyzed over a period of historical data    in the Telangana state( India ) and Godavari of sub basin. The aim of this paper is analyzing the flood and drought of study areas based on the intensity of the precipitation from historical data   and   The result obtained from this analysis is presented in form graphs . The Godavari flood and drought scenarios are very important to analyze the study area to  protect the  natural disasters and  also to take preventive measures for  the future floods  and droughts. Some data has collected   from the Government agencies to obtain the better result. The study area   has total 141 number weather stations.  Important weather stations where is collected maximum precipitation and least, average precipitation data has used for the analysis. The results available are presented in the form of graphs and numerical evaluation. Study is carried out in the G5, G6, G10 (Godavari sub Basin5, Godavari sub Basin6, Godavari sub Basin10  ) Godavari sub Basin